Hieronymi Fracastorii: the Italian scientist who described the "French disease" - Filippo Pesapane; Stefano Marcelli; Gianluca Nazzaro (Sociedade Brasileira de Dermatologia, 2015)
AbstractGirolamo Fracastoro was a true Italian Renaissance man: he excelled in literature, poetry, music, geography, geology, philosophy, astronomy and, of course, medicine to the point that made Charles-Edward Armory Winslow define him as "a peak unequaled by anyone between Hippocrates and Pasteur". In 1521 Fracastoro wrote the poem "Syphilis Sive de Morbo Gallico" in which was established the use of the term "syphilis" for this terrible and inexplicably transmitted disease, often referred to as "French disease" by the people of the time and by Fracastoro himself.